A Female Hair Clip and Orthodontists' Neck-Back Pain Perception: A Survey - Arkan Muslim Al Azzawi; Hasan Sabah Hasan; Mohammed Nahidh; Mohamed Elkolaly; Ayshan Kolemen (Hindawi Limited, 2021)
This study aimed to clarify the effect of large hair clips on patient head posture on the dental chair headrest and its harmful impact on orthodontist body posture and neck-back pain. One hundred orthodontists voluntarily participated in a web-based questionnaire designed and distributed online by using the Google form posted in the Telegram group of Iraqi orthodontists to assess the opinions of orthodontists regarding the effect of a large hair clip on the patient's position on the dental chair and site of pain perception during different stages of orthodontic treatment. Ninety percent of the orthodontists get bothered by the large hair clip. About 92% of the responses preferred their patients to remove the large hair clip; 99% of them responded that the large hair clip does affect the position of the patient's head on the chair's headrest. Eighty-nine percent responded that a large hair clip could disturb the operator during taking intraoral photographs, and 64% disturbed while taking dental impressions. Orthodontists reported that 4% had "back pain," 28% had "neck pain," and 60% had both "back and neck pain" during bonding appointment, while only 8% reported "no pain." Regarding the activation appointments, 4% had "back pain," 26% had "neck pain," and 48% had both, while only 22% reported "no pain." During the debonding appointments, 7% of the respondents had "back pain," 29% had "neck pain," and 44% had both "back and neck pain," yet 20% stated absence of pain. Wearing a hair clip and changing patient position on dental chair and orthodontist posture during different stages of orthodontic work such as bonding, regular recall, and depending on the procedure may be directly related to the neck-back pain perception to an orthodontist.